Plastic pollution: about time to unify research methods and demand systemic changes - Hellevik, Christina Carrozzo; Cyvin, Jakob Bonnevie (Frontiers in Environmental Science, 2023)
The issue of plastic pollution is recognised as a pervasive and ubiquitous problem which can pose a threat to ecosystems worldwide and potentially affect human health. In this perspective, we selected the latest research that identifies potential impacts beyond individual species to draw attention on wider biogeochemical cycles and the most fundamental biological processes we all depend on, namely breathing, feeding and carrying offspring. We highlight the need for uniform research methods, giving examples of protocols and indicator species that should be evaluated by the research community for their potential wide adoption. We further stress the need for systemic changes and our role as scientific community to demand changes proportionate to the severity and implications of our findings. We further explore the push and pull mechanisms between researchers and policy-makers in relation to the global environmental issues such as plastic pollution. Finally, we recommend a path of action inspired by the global action taken to address the ozone layer depletion by banning chlorofluorocarbons (CFC).